The Effect Of Work Motivation And Discipline On Employee Productivity At J&T Express DC Ciledug, Tangerang City - Dewi Sartika (Doctoral Program of Social Science Pasundan University, 2025)
This study aims to determine the effect of motivation and work discipline on employee productivity at J&T Express DC Ciledug, Tangerang City. The method used is explanatory research with sampling using saturated samples where all members of the population are used as samples so that the sample in this study amounted to 67 respondents and data analysis techniques using statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study indicate that motivation has a positive and significant effect on employee productivity as evidenced by the hypothesis test obtained t count> t table or (6.679> 1.997) with an influence contribution of 41.1%. Work discipline has a positive and significant effect on employee productivity as evidenced by the hypothesis test obtained t count> t table or (7.305> 1.997) with an influence contribution of 45.5%. Motivation and work discipline simultaneously have a positive and significant effect on employee productivity, as proven by the hypothesis test, which obtained F count > F table or (51.355 > 2.750) and the regression equation Y = 6.318 + 0.364X1 + 0.509X2 was obtained and had a contribution effect of 62.0%.